Wing geometry analysis as a potential tool for species identification for Anopheles mosquitoes (Diptera: Culicidae) in Indonesia - Nugroho, Sidiq Setyo; Mujiyono,; Siswoko, Sapto Prihasto; Prasetyo, Arif Suryo; Garjito, Triwibowo Ambar (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2020)
In the last decade, wing geometry has been investigated intensively as an alternative powerful method for solving taxonomic problems in insects. The objectives of this research were to describe wing geometry variation among seven Anopheles species and to confirm the sensitivity of wing geometry analysis for identifying single specimen of Anopheles mosquito. Thus, the potential of wing geometry analysis as an alternative tool for species identification for Anopheles mosquitoes can be recognized. Left wing of seven Anopheles species were detached and photographed. Wing geometry was represented by 18 landmarks (LMs). Wing geometry analysis was conducted by MorphoJ and tps software series. Comparison among species and identification simulation were done using canonical variate analysis (CVA). Wing geometry was successfully discriminated and grouped seven Anopheles species into correct subgenera and series. This method also gave good results in identifying single specimen. Nine out of 11 specimens (81, 8%) obtained identification results that match their phylogenetic relationships. Weakness using wing geometry in species identification can be overcome by adding template species. In conclusion, wing geometry analysis has good potential to be used as an alternative tool for species identification for Anopheles mosquito in Indonesia.